IN VITRO ANTI-OXIDANT AND ANTI-BACTERIAL ACTIVITY OF SODIUM COPPER CHLOROPHYLLIN FROM LEUCAS ASPERA L. - GEETHA RANI. R,; BANU. N, (International Journal of Pharma and Bio Sciences, 2016)
Leucas aspera L. commonly known as ‘Thumbai’ is distributed throughout India. The plant is used traditionally as an antipyretic and insecticide. Medicinally, it has been proven to possess various pharmacological activities like antifungal, antioxidant, antimicrobial, antinociceptive and cytotoxic activity. The leaf extracts of Leucas aspera L. shows significant anti-oxidant and anti-bacterial activity against Klebsiella pneumonia and Staphylococcus aureus. The antioxidant activities of Lucas aspera L. were observed by a change in colour from yellow to green with different concentrations (100-600µl). The antibacterial activities of Leucas aspera L. Were screened against two infectious pathogens, by the agar disc diffusion method. Ampicillin (10 μg /ml) was used as positive control. The antibacterial activity of Leucas aspera L. showed active inhibition against the tested human pathogens.